2010
DOI: 10.1084/jem.20101095
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-induced selective loss of leukemia-initiating activity in murine adult T cell leukemia

Abstract: Treatment with a combination of interferon-α and arsenic trioxide ablates leukemia-initiating activity before reducing primary tumor bulk in a murine model of adult T cell leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(121 citation statements)
references
References 28 publications
9
112
0
Order By: Relevance
“…Transplantation studies have demonstrated that even a very brief treatment, which does not impair in vivo tumor growth or proliferation, abrogates the capacity of leukemia to engraft in secondary hosts, provided that the proteasome is functioning (ref. 65; Fig. 3C ).…”
Section: Breast Cancermentioning
confidence: 91%
See 1 more Smart Citation
“…Transplantation studies have demonstrated that even a very brief treatment, which does not impair in vivo tumor growth or proliferation, abrogates the capacity of leukemia to engraft in secondary hosts, provided that the proteasome is functioning (ref. 65; Fig. 3C ).…”
Section: Breast Cancermentioning
confidence: 91%
“…Yet, the oldest example of targeted therapy, is strongly suggested by the recent report that this combination can cure murine ATL derived from Tax-transgenic mice ( 65 ). Because the action of the IFN-α/arsenic combination is very specific to both HTLVI-infected human cells and Tax-driven murine leukemia, it is most likely that therapy-induced loss of the driving oncogene underlies responsiveness to therapy ( Fig.…”
Section: Breast Cancermentioning
confidence: 99%
“…Importantly the combination of interferon and arsenic has unambiguous clinical benefit in HTLV-1 infected Adult T-Cell Leukemia (ATL) patients, where remissions can be achieved in the absence of chemotherapy. 122,123 Spinocerebellar ataxia (SCA1) is caused by accumulation of ataxin 1, a poly-glutamine stretch containing protein, which is degraded by the PML/SUMO/RNF4 system. 90 Interferon treatment can induce clearance of ataxin 7 from the brain in a PMLor SUMO-dependent manner, resulting in clinical benefit.…”
Section: The Interferon Connection and Medical Implicationsmentioning
confidence: 99%
“…IFNs induce a transient global polyubiquitination 61 , which could result from the hypersumoylation unravelled here. These findings have important therapeutic relevance, as IFNa promotes PML-and SUMO-dependent degradation of toxic proteins in the brain 62,63 or of the HTLV-I leukemia oncoprotein Tax 64 , with unambiguous clinical benefit 62,65,66 . Thus, similar to therapies based on manipulation of ubiquitin-dependent degradation 67,68 , this could pave the way to IFN-triggered, SUMO-based therapies promoting the proteolytic clearance of undesirable proteins 68 .…”
Section: Articlementioning
confidence: 99%